SYMBOLISM - COMPREHENSION RELATIONSHIP IN SCHOOL LEARNING - CORNELIA STAN (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. In everyday life, comprehension phase message induces interest of knowledge itself, the surrounding world, empowering, interpreted, skill formation to guess/search for meanings/multiple correlations between notions, facts, phenomena. Communication with and through symbols, in concrete operative phase of thinking can trigger the transition to formal operative phase, the abstraction and generalization. Iconic and symbolic communication occupies a growing share in the instructive-educational, thanks largely to technical means of training (videoprojectors, interactive whiteboards). Thus is born a series of questions such as: how does the image, respectively the symbol, at the cognitive development as well as to educating experience affective-emotional needs of students? To what extent determines the quality of social interactions symbols?